Assessment of executive functions in children and adolescents with acquired brain injury (ABI) using a novel complex multi-tasking computerised task: The Jansari assessment of Executive Functions for Children (JEF-C©). Issue 9 (21st October 2019) - Gilboa, Yafit; Jansari, Ashok; Kerrouche, Bernadette; Uçak, Emel; Tiberghien, Anne; Benkhaled, Ouarda; Aligon, Delphine; Mariller, Aude; Verdier, Valentine; Mintegui, Amaia; Abada, Geneviève; Canizares, Céline; et al.
ABSTRACT: Objectives: The Jansari assessment of Executive Functions for Children (JEF-C © ) is a new non-immersive computerised assessment of executive functions. The objectives of the study were to test the feasibility and validity of JEF-C © in children and adolescents with acquired brain injury (ABI). Methods: Twenty-nine patients with ABI aged 10–18 years and 30 age-and gender-matched controls were tested. Participants performed JEF-C ©, Wechsler Abbreviated Scale of Intelligence (WASI) and the Behavioural Assessment of the Dysexecutive Syndrome for Children (BADS-C), while parents completed the Behaviour Rating Inventory of Executive Function (BRIEF) questionnaire. Results: The JEF-C © task proved feasible in patients with ABI. The internal consistency was medium (Cronbach's alpha = 0.62 and significant intercorrelations between individual JEF-C © constructs). Patients performed significantly worse than controls on most of the JEF-C © subscales and total score, with 41.4% of participants with ABI classified as having severe executive dysfunction. No significant correlations were found between JEF-C © total score, the BRIEF indices, and the BADS-C. Significant correlations were found between JEF-C © and demographic characteristics of the sample and intellectual ability, but not with severity/medical variables. Conclusion: JEF-C © is a playful complex task that appears to be a sensitive and ecologically valid assessment tool, especially for relatively high-functioning individuals.